Laser Assisted Root Canal Disinfection-A Review - Purayil, Tina Puthen; Chakravarthy, Arumugam; Ballal, Nidambur Vasudev; Varghese, Jothi (The Journal of Dentists, 2016)
Laser assisted procedures evoked the field of endodontics almost 3-4 decades ago by means of using appropriate energy produced by light for alteration of various hard and soft tissues. During the initial years, the cumbersome laser delivery systems and handling limited its use, despite the purported advantages. However, the last few years, have seen tremendous advancements in terms of tip designs, disinfection agents, photoacoustic streaming etc. This paper has been compiled in an attempt to discuss the effects of photo-activated technology on the root canal system.